Is it necessary to ingest carbohydrates and fluids during 10 km open water swimming in top-level competitions? - Olcina, G.; Timón, R.; González-Pérez, I. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
Open-water swimming (OWS) is an Olympic discipline in the distance of 10 km. Usually, competitions are based on 4 or 5 laps where in each of them swimmers have the option to stop in the feed zone to intake some food or fluids or continue swimming. The choice made may have some tactical or physiological implications. The aim of this study was to evaluate the physiological consequences of a pre-programmed race nutrition plan in top-level open-water swimmers to know whether it can be skipped or whether it should be necessary. In three different competitions (LEN open-water cup, FINA world marathon series and FINA world championships) 22 swimmers belonging to the National Spanish Team were recruited (13 males and 9 females). PRE- and POST-race blood glucose (mg/dl) and body weight (kg) were measured. Carbohydrate (CHO) and fluid ingestion during the race was recorded and sweat rate (l/h) was calculated. Blood lactate (mmol/L) was determined 5 minutes after finishing the event. T-test for comparing PRE/POST data and bivariate Pearson correlation test for all variables were used. For an average 2 h duration of swimming races with a water temperature of 23±3°C, swimmers ingested 500 ml of fluid +30 g CHO between 15` before starting and 500-750 ml of fluid?+?90 g CHO during the race. Sweat rate was 1.09±0.46 L/h, body weight decreased after competition (PRE 71.55±7.54 vs POST 70.90±7.61, p<0.001), finish lactate was 4.1±1.9 mmol/L and blood glucose (mg/dl) increased from PRE 100 ±11 to POST 120±27, p<0.002. Lactate correlated with POST glucose (r=0.629, p<0.001) as well as the position in overall classification correlated with POST glucose (r=0.640, p<0.001). However, in the world championships event, stronger correlations were found between overall classification and finish glucose (r=0.958, p<0.05) and between POST glucose and finish lactate (r=0.955, p<0.05). These data suggest that fluid replacement during OWS-10 km races is not as important as CHO ingestion, due to the importance of CHO metabolism. With this information, coaches and swimmers may develop different race nutritional plans that guarantee CHO ingestion and do not compromise tactical actions during competition. This work has been supported by Royal Spanish Swimming Federation and the Government of Extremadura (Ref: GR18003).